2017
DOI: 10.1016/j.jacc.2017.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinidine Prevents Life-Threatening Arrhythmic Events in Patients With Short QT Syndrome

Abstract: We demonstrated for the first time that treatment with HQ was associated with a lower incidence of LAE in SQTS patients. These data point to the importance that quinidine, that in several countries has been removed from the market, remains available worldwide for patients with SQTS. In the present study, therapy with HQ has been proven to be safe, with a relatively low rate of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Importantly, (hydro)quinidine has recently also been confirmed to be associated with prevention of life‐threatening arrhythmic events in SQTS patients (Mazzanti et al. ). For the N558K mutation at least, simulation data suggest that the beneficial actions of quinidine on effective refractory period result from both I hERG / I Kr inhibition and the drug's Na channel inhibitory action (Whittaker et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, (hydro)quinidine has recently also been confirmed to be associated with prevention of life‐threatening arrhythmic events in SQTS patients (Mazzanti et al. ). For the N558K mutation at least, simulation data suggest that the beneficial actions of quinidine on effective refractory period result from both I hERG / I Kr inhibition and the drug's Na channel inhibitory action (Whittaker et al.…”
Section: Discussionmentioning
confidence: 99%
“…Issues with (hydro)quinidine availability in some countries (Mazzanti et al. ) may be problematic for its use, however. In relation to this, it is worth highlighting that conventional voltage clamp experiments have shown that the Class Ia agent disopyramide also retains effectiveness against the S631A mutation (Paul et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, an indication should be evaluated by a referral centre with good experience in SQTS (El-Battrawy et al, 2019). In addition, recently published data have shown that hydroquinidine prevent arrhythmias (Giustetto et al, 2011;Mazzanti et al, 2017). Other antiarrhythmics such as carvediol, metoprolol, and sotalol do not have the same effect as hydroquinidine (El-Battrawy et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%